Strengthening Character Education through Critical Culture in the Era of Revolution 5.0 - Arip Amin; Diding Nurdin; Suryadi; Djam’an Satori (Universitas Lancang Kuning, 2023)
The era of revolution 5.0 is a concept of society based on technology. Various challenges arise in the era of revolution 5.0 which requires each individual to have special skills and abilities, including the ability to think critically, creatively and innovatively and have good character as a control in utilizing technology. This service aims to provide strengthening of character education to every individual, especially students who are part of society so that they can have good ethics as a characteristic of Indonesian national identity. The service was carried out in the form of a scientific oration involving 55 participants who were students representing the Student Executive Board for the West Java Region. The results of the service show that critical culture as student character education is very important as a provision to face various challenges of the 5.0 revolution era. Critical culture becomes one of the traits in student character development to prevent the destruction of young morals from being degraded by bad choices